Influence of Plastic Deformation and Hydroxyapatite Coating on Structure, Mechanical, Corrosion, Antibacterial and Cell Viability Properties of Zinc Based Biodegradable Alloys - Aksakal, B.; Isin, Ege; Aslan, N.; Cihangir, S.; Sezek, S. (Korean Inst Metals Materials, 2024)
Zinc (Zn)-based biodegradable alloys have been at the forefront of absorbable biomaterial research in recent years due to their high biocompatibility and corrosion rates. The arc melting process was used to produce the Zn-1Cu-1Ag biodegradable alloy. The influence of different plastic deformation rates on the microstructure of the material was examined after the cold rolling at deformation rates of 47% and 61%. The undeformed and deformed alloys have been hydroxyapatite-coated using the electrophoretic deposition process to improve its surface, corrosion, and bioactivity properties. Optical, XRD, SEM, and EDS examinations were used to analyze the samples' uncoated, coated, and rolled-unrolled forms. The nucleation of the (Ag, Cu)Zn4 secondary phase was formed during the rolling process. Hardness and compression tests were used to determine the mechanical properties of cast and rolled alloys, and in vitro corrosion tests were carried out in simulated body fluid. Antimicrobial and cell viability tests are executed to demonstrate the biocompatibility of the deformed and HA-coated Zn-1Cu-1Ag alloy. The mechanical properties were improved after the rolling process, with the highest results found in 47% of the rolled samples exhibiting a compressive strength of 412.65 +/- 0.5 MPa and 61% of the rolled samples exhibiting a hardness value of 88.1 +/- 0.5 HV. The samples that were rolled (61%) and coated with hydroxyapatite (HA) exhibited the highest level of corrosion resistance. The antimicrobial tests revealed that the rolled and HA coated Zn1Cu1Ag groups exhibited greater inhibition rates (47 and 61%) compared to the other groups when tested against E. coli. The HA-coated groups exhibited good cell viability ratios, with the maximum viability seen in the rolled and HA-coated group at 47%.
Keywords: Biodegradable metals; Zn-1Cu1Ag; Rolling; EPD coating; Corrosion; Cell viability